Debunking the local government malaise under the decentralization policyin Uganda: an analytical treatise - Julius, Chama (Kabale University Interdisciplinary Research Journal (KURJ), 2023)
Several years have passed since Uganda approved decentralization both as a tool of good governance and as a policy of poverty reduction however many regions and districts in the country, including the city authorities, continue to stagger in poverty and development melancholy. Studies conducted at the local/district level show that high levels of poorness and underdevelopment remain. This development paradox is the subject of this article. A review of the current literature and interviews with stakeholders in local government institutions in Uganda, unveil that conflicts, limited resources and continued fragmentation of districts by politicians have been impediments to progress. Hindrances also included the socio-economic and the political. It also portrays gerrymandering and a decrepit state of affairs. This study suggests the sovereignty of local governments, expansion of resource bases through robust methods such as taxation and the institutionalization of public sector reform programs to ensure a sustainable base for social services delivery